Keragaman Genetik Peronosclerospora maydis Penyebab Bulai pada Jagung Berdasarkan Analisis Marka SSR - Muis, Amran; Pabendon, Marcia B.; Nonci, Nurnina; Waskito, Wahyu Purbowasito (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2013)
Downy mildew on maize in Indonesia had been reported infecting maize in all provinces and they are mostly caused by Peronosclerospora maydis, except in Sulawesi which is caused by P. philippinensis. The disease spreads very quickly because the conidia could be dispersed by the air movement. This study was aimed to determine the genetic diversity of the downy mildew pathogen in Indonesia using SSR markers, conducted from April to October 2012. The pathogens were sampled by collecting plants infected by downy mildew from Aceh, North Sumatra, Lampung, West Kalimantan, West Java, East Java and South Sulawesi. The SSR analysis results showed that the genetic similarity coefficient among the 67 isolates were quite high and the isolates formed three clusters, i.e. clusters A, B, and C and two sub-clusters within cluster A based on UPGMA, which were fairly obvious grouping of isolates based on conidial morphology. The sub-cluster A1, conidia shape was similar to that of P. philippinensis from South Sulawesi geographical area. The sub-cluster A2, conidia shape was similar to that of P. maydis from East Java, West Kalimantan, and Lampung. Cluster B consisted collection of pathogen DNA from specific areas, namely Aceh, Toraja and Simalungun (North Sumatra). Cluster C which formed conidia resemble to that of P. sorghi, derived from Langkat (North Sumatra) and Bogor (West Java).